THE RIVERS, THE CITY AND THE MAP AS OBJECT OF LANDSCAPE DYNAMICS ANALYSIS - Santos, Kairo da Silva; Antunes, Fernando de Souza; Fernandes, Manoel do Couto (Mercator; Vol 18 (2019), 2019)
Historical cartography has been increasingly important in understanding the landscape transformations, especially in the urban environment where different historical records are used. The present work aims at identifying and comparing, from historical and current records, the changes occurred in the three main rivers that cut the genesis area of the city of Petrópolis (Quitandinha, Palatino and Piabanha). The main research material consists of the Koeler Map (1846), a document that guides the urban planning of the city of Petrópolis, which was designed in line with the drainage network, produced in a 1: 5,000 scale and the most recent cartographic base of the city (1999) in scale 1: 10,000. The georeferencing and vectorization of the Koeler Map made it possible to perform different measurements, such as river width and winding. Later, the same procedures were performed on the most recent cartographic base of the city, in order to create comparative parameters for changes in the course of the rivers and their floods. The results show the suppression of four river islands and a decrease of sinuosity of the rivers with a variation of +0.575% to -2.436%. In the Quitandinha river were recorded the biggest changes and the largest flood record (97%), indicating that changes in the drainage network are significant elements in understanding flood dynamics. Keywords : Landscape change. Drainage network. Koeler Map. Historical GIS. Keywords : Landscape change. Drainage network. Koeler Map. Historical GIS.